A)-1,3. (7+ 4x) - 11 = -4,5;
6) (x - 2,3)*X = 4x

tanyabilotserko tanyabilotserko    2   01.03.2021 20:14    0

Ответы
rimmochkapups9p0dicd rimmochkapups9p0dicd  31.03.2021 20:15

Пошаговое объяснение:

6)

Х^2-2,3х=4х

х^2-2,3x-4x=0

Дальше решаем квадратное уравнение

x=0. x=63/10

A) -9,1-5,2x-11=-4,5

-5,2x=15,6

x=-3

ПОКАЗАТЬ ОТВЕТЫ
Irina5786 Irina5786  31.03.2021 20:15

-1,3×(7+4x)-11=-4,5

-9,1-5,2x-11=-4,5

-5,2x=-4,5+9,1+11

-5,2x=15,6

x=15,6÷-5,2

x=-3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика